VALLABHA, VAISNAVISM AND THE WESTERN HEGEMONY OF INDIAN THOUGHT - Timm, Jeffrey R (Journal of Dharma, 1989)
Anyone who has spent time in Northern India - from Banaras to Delhi to Ahmedabad - has seen the image of Sri Govardhana Näthaji. Plumed headpiece set at a rakish angle, thickly garlanded with jeweled necklaces, Sri Näthaji peers through slit-like eyes, left arm raised to hold aloft the idea of Govardhana hillock, protecting his devotees. The pose captures the moment from Krishna's story found in the Bhägavata Puräžga X. 25; a story beloved to the Vaisqavas who count themselves members of the Vallabha community stretching beyond the Hindi-belt into Gujarat and Maharashtra. But who is this dark-faced deity